Fiscal Stimulus and Micro and Small Enterprise Resilience during the Covid19 Pandemic in Riau - Mardiana, Mardiana; Eriyati, Eriyati; Iyan, Ritayani; Indrawati, Toti; Tampubolon, Dahlan (Budapest International Research and Critics University, 2022)
This article aims to obtain an overview of the fiscal stimulus and conditions of micro and small businesses in Riau. Field research for 4 (four) months, from June 2021 to September 2021. This study uses primary data obtained from distributing questionnaires to micro and small businesses in Riau. This study purposively selected 75 respondents with equal proportions in all districts and cities. In Riau, in 2020, micro-enterprise financing reached Rp. 23.7 billion, the most in Pekanbaru City and the least in Kuantan Singingi. Most of the micro and small business actors who received a fiscal stimulus from the government did not have other jobs and had been in business for more than one year. The main business carried out is the trade sector and services, with the most places of business being at home. Generally, small and micro business actors do not get bank loans and KUR. They use their capital and informal loans. They obtained information on stimulus assistance from the government and its officials, the media, banks, and cooperatives. Most of the stimulus assistance proponents came from the offices, cooperatives, and banks.